Experimental Investigation Of EDM Die Sinking Process Parameters On Aluminium Alloy 5083 Using Design Of Experiment - Wahaizad, Safiei; Muhamad Ridzuan, Radin Muhamad Amin (Penerbit Universiti Malaysia Pahang, 2017)
In this paper, the results of surface roughness (Ra) and material removal rate (MRR) are presented based on experimental studies of Electrical Dischar ge Machining (EDM) process parameters. Pulse ON time, pulse OFF time, peak current, gap voltage and jump speed are the selected input parameters and the experiments were conducted with Aluminium Alloy 5083 as a workpiece, copper as an electrode and the response variables are surface roughness (Ra) and material removal rate (MRR). Design of Experiment and Analysis of Variance (ANOVA) were applied to identify the optimum settings.The result shows that the significant factors for the value of surface roughness (Ra) and material removal rate (MRR) are pulses ON time and peak current.